PENGARUH KEPUASAN KERJA, LINGKUNGAN KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DI PT. MAS SUMBIRI - Agus Dwi Anggoro, 11.05.51.0002 (Students Journal of Economic and Management, 2015)
The research is done in PT. Mas Sumbiri that located in Campurejo Village, Boja District, Kendal Regency on September untill October 2014. The research has purpose to know about the influence of work satisfaction, work environment, and organization culture to employeeâs working in PT. Mas Sumbiri A method of taking samples using purposive sampling withÂ the total sample used are 100 employees. As independent variabels are work satisfaction, work environment, and organization culture, meanwhile dependent variabel is employeeâs working. Relation and or influence between each variabel explained byÂ multiple regression analysis. The results of research show that work satisfaction has positive influence and significant of employeeâs working, itâs be proven from the t-count value is 2,148 and by using the level of significant for 5% obtained t-table value 1,671, which means that t-count value more than t-table value, they are 2,148 > 1,671 and the significant 0,034 < 0,05. Work environment has positive influence and significant of employeeâs working, itâs be proven from the t-count value is 4,513 by using the level of significant for 5% obtained t-table value 1,671, which means that t-count value more than t-table value, they are 4,513 > 1,671 and the significant 0,000 < 0,05. And organization culture has positive influence and significant of employeeâs working, itâs be proven from the t-count value is 3,388 by using the level of significant for 5% obtained t-table value 1,671, which means that t-count value more than t-table value, they are 3,388Â > 1,671 and the significant 0,001 < 0,05. All variable also have positive influence and significant of employeeâs working in PT. Mas Sumbiri simultantly. Itâs be proven from the F-test value is 74,894 and the significant is 0,000. Beside that, from the determination analysis get output that work satisfaction, work environment, and organization culture, can explain dependent variabel or employeeâs working amounted to 69,1%, meanwhile for 30,9% be influenced by other variabels outside of variabels to be researched. Keyword:Â work satisfaction, work environment, organization culture, dan employeeâs working